2023
DOI: 10.3390/v15040847
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Antiviral Potential of Phytocompounds against Avian Infectious Bronchitis Virus through Template-Based Molecular Docking and Molecular Dynamics Simulation Analysis

Abstract: Vaccination is widely used to control Infectious Bronchitis in poultry; however, the limited cross-protection and safety issues associated with these vaccines can lead to vaccination failures. Keeping these limitations in mind, the current study explored the antiviral potential of phytocompounds against the Infectious Bronchitis virus using in silico approaches. A total of 1300 phytocompounds derived from fourteen botanicals were screened for their potential ability to inhibit the main protease, papain-like pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…A related RA derivative, MR, can be obtained by esterification of RA with methanol under the catalysis of hydrochloric acid, is structurally similar to RA, but differs in the esterification of the side chain carboxyl groups, imparting a greater lipid solubility. Current activity studies on MR have mainly demonstrated its antitumor, antibacterial, antioxidant, anti-glycosylation, and anti-inflammatory effects ( Lin et al, 2013 ; So et al, 2016 ; Nam et al, 2019 ; Gul et al, 2023 ). However, its anti-pulmonary fibrosis effects and mechanisms have not been described.…”
Section: Introductionmentioning
confidence: 99%
“…A related RA derivative, MR, can be obtained by esterification of RA with methanol under the catalysis of hydrochloric acid, is structurally similar to RA, but differs in the esterification of the side chain carboxyl groups, imparting a greater lipid solubility. Current activity studies on MR have mainly demonstrated its antitumor, antibacterial, antioxidant, anti-glycosylation, and anti-inflammatory effects ( Lin et al, 2013 ; So et al, 2016 ; Nam et al, 2019 ; Gul et al, 2023 ). However, its anti-pulmonary fibrosis effects and mechanisms have not been described.…”
Section: Introductionmentioning
confidence: 99%